Balancing development and sustainability in tourism destinations : proceedings of the Tourism Outlook Conference 2015 - Saufi, Akhmad; Andilolo, Imanuella R.; Othman, Norain; Lew, Alan A. (Springer, 2017)
This book contains 35 papers from the Tourism Outlook Conference held in Lombok, Indonesia in July 2015. The book presents comprehensive discussions on sustainability in the tourism industry. It includes research on various constituents of the tourism sector and analyses of each of them from a sustainability standpoint. Case studies that are global in nature are presented to show how sustainable applications can be used and how concerns can be addressed. The book is a response to rapid change in contemporary tourism trends brought about by global economic and social forces such as development pressures, population growth, major resource extraction, industrial fishing, global climate change and steadily rising sea levels. Balancing Development and Sustainability in Tourism Destinations serves as a platform for students and educators, government agency employees, hospitality and tourism industry practitioners, public and private land managers, community development workers, and others interested in identifying practical solutions, charting new directions, and creating opportunities for sustainable tourism development.